Effects of clonidine injections into the bed nucleus of the stria terminalis on fear and anxiety behavior in rats. - Schweimer, J; Fendt, M; Schnitzler, H (2005)
Emotions such as fear and anxiety are mediated by a neural network containing nuclei like the amygdala, the bed nucleus of the stria terminalis and the periaqueductal gray. Noradrenaline is a neurotransmitter closely connected with the processing of stimuli eliciting these emotions. The bed nucleus of the stria terminalis contains the highest density of noradrenaline within the brain. In the present study, we investigated effects of injections of the noradrenergic alpha2-adrenoceptor agonist clonidine into the bed nucleus of the stria terminalis on learned and unlearned fear (anxiety) in rats on different animal models of fear and anxiety: acquisition and expression of fear-potentiated startle, sensitization of the acoustic startle response by foot shocks and light-enhanced startle. Clonidine injections disrupted acquisition and expression of fear-potentiated startle, as well as light-enhanced startle, whereas sensitization was not affected. These results indicate that noradrenaline within the bed nucleus of the stria terminalis mediates both fear and anxiety. We suggest that there is rather a neurochemical than a neuroanatomical dissociation between learned fear and anxiety as hypothesized by Walker and Davis (Walker, D.L. and M. Davis, 1997b, Double dissociation between the involvement of the bed nucleus of the stria terminalis and the central nucleus of the amygdala in startle increases produced by conditioned versus unconditioned fear, J. Neurosci. 17, 9375-9383.).